Effects of short-term altitude training and tapering on left ventricular morphology in elite swimmers - Haykowsky, M. J.; Smith, D. J.; Malley, L.; Norris, S. R.; Smith, E. R. (Canadian Journal of Cardiology, 1998)
Short or long-term athletic training has been associated with left ventricular (LV) morphological adaptations, including increases in wall thickness, cavity dimension and estimated LV mass. A limitation of previous studies assessing the "athlete heart" was that exercise training was performed at sea level. Since the 1968 Olympic summer games a popular method of maximizing athletic performance has been to use altitude training (AT) as a means of improving sea level performance. However, the effect of short term AT and taper training on left ventricle morphology has not been well studied. Because on that inadequacy the effects of three weeks of intense AT (1,848 m) or low level control training (CT) (1,050 m) followed by two weeks of taper training were investigated in elite swimmers (N = 15) aged between 16 and 21 years. Short term AT or CT training followed by two weeks of taper training was not associated with alterations in LV diastolic cavity dimension, ventricular septal wall thickness, estimated LV mass, or fractional shortening. However, a main time effect, independent of training intervention, was observed for posterior wall thickness (pre 8.7 + 1.4 mm versus post 9.3 + 1.1 mm, p < 0.05). With the exception of posterior wall thickness, short term AT followed by two weeks of taper training appears not to be associated with alterations in LV morphology or systolic function. Implication: Short-term (three weeks) altitude training does not affect overall ventricular structure in swimmers.